Policy Recommendations to Enhance Vietnamese SMEs’ Ability to Access Venture Capital - Thao, Dam Thi Phuong (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 2, 2022)
Small and medium enterprises, which form a large part of the entity of the domestic private sector, play a vital role in economic growth, socio-economic development and the international integration process. However, SME groups in developing countries are under-developed and face a lot of difficulties in growth due to the absence of sufficient finance. Profoundly, venture capital is typically a suitable and sustainable external source of finance for Vietnamese SMEs with high growth potential. This study provides an overview of the venture capital market and its role in SMEs’ performance in Vietnam. This research also found that one of the reasons why foreign investment funds are not interested in the Vietnamese market is that they have not seen safe and sustainable opportunities for investment. This study not only contributes to the existing literature, because this topic in Vietnam has not received much attention and evidence is not available, but also gives policymakers, in developing countries in general and Vietnam in particular, some recommendations to determine areas of improvement in regulatory and policy aspects enabling increased responsible SME access to venture capital.